Studi Deskriptif Kepemilikan Modal Kewirausahaan dalam Pendirian Usaha Rintisan Baru - Hermawan Kahfi, Iwan; Kusmulyono, Muhammad Setiawan (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2019)
This descriptive study was conducted to see the relationship between the entrepreneurial capital ownership and the establishment of new startups. Through the subject study entitled Entrepreneurial Capital in Prasetiya Mulya's S1 Business program, student assigned to mapping their entrepreneurial capital, formed group and proposed a startup idea. To answer whether optimization of entrepreneurial capital contributes to success the establishment of new startups, we make a quantitative approach by analyzing the data obtained from the assessment of the final exam business ideas, and entrepreneurial capital of group, as well as qualitative assessments of each aspect of capital entrepreneurship tested. Final assessment shows that 109 groups formed has sufficient entrepreneurial capital to running new startups in 9 selected business fields. The lowest score in the food and beverage business shows that entrepreneurial capital in this area is not difficult. In certain area such as in chemical businesses, more entrepreneurial capital is comprehensively and completely needed. Further study need to do by studying the journey of each group, in completing the final project business project for the next one year.